2007
DOI: 10.2741/2065
|View full text |Cite
|
Sign up to set email alerts
|

Molecular control of ovulation and luteinization in the primate follicle

Abstract: In recent years, significant progress was made, particularly through the use of the macaque monkey, in identifying three types of local factors that are induced by the midcycle LH surge and play a critical role in ovulation and/or luteinization of the primate follicle. The ovulatory gonadotropin surge increases prostaglandin (PTG, typically abbreviated PG) levels in follicles prior to rupture; although considerable attention has focused on LH stimulation of the "inducible" form of PG G/H synthase (PTGS2), othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(60 citation statements)
references
References 76 publications
4
56
0
Order By: Relevance
“…The effect of reduced ADA activity on follicular development is not clear. There is evidence that vasodilation and high vascular permeability play a curial role during the ovulatory event in humans, and also ADA activity diminishes the amount of adenosine, deteriorating its vascular effect during follicular phase [9,43]. However, a recent study evaluated follicular fluid adenosine concentration in women who undergoing ovarian stimulation indicated that there is no functional ADA in the follicular environment of mature oocyte [44].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of reduced ADA activity on follicular development is not clear. There is evidence that vasodilation and high vascular permeability play a curial role during the ovulatory event in humans, and also ADA activity diminishes the amount of adenosine, deteriorating its vascular effect during follicular phase [9,43]. However, a recent study evaluated follicular fluid adenosine concentration in women who undergoing ovarian stimulation indicated that there is no functional ADA in the follicular environment of mature oocyte [44].…”
Section: Discussionmentioning
confidence: 99%
“…Two positive controls were used at the same concentration as experimental siRNAs; one siRNA targeted GAPDH mRNA (Silencer GAPDH siRNA, Ambion) and the other targeted CDC2 mRNA (Santa Cruz Biotechnology, Inc., Santa Cruz, CA, USA), whose presence in the ovary has been previously demonstrated (Sirotkin & Grossmann 2006, Stouffer et al 2007.…”
Section: Oligonucleotidesmentioning
confidence: 99%
“…The stimulatory effects of these growth factors on maturation of the oocyte (Sirotkin et al 2000a,b,c), of Cumulus oophorus and embryo development (Makarevich et al 2000) are mediated through PKA. P 4 prevents apoptosis, maintains survival, and promotes proliferation of ovarian granulosa cells via the PKG-dependent (Peluso 2003) and CDK-dependent (Stouffer et al 2007) pathways.…”
Section: Introductionmentioning
confidence: 99%
“…In mice and rhesus monkeys, MMPs are up-regulated during the transformation of follicular granulosa cells into functional luteal tissue, and again during luteal regression (Young and Stouffer, 2003;Liu et al, 1999). In addition to physical remodeling, the cleavage action of ovarian MMPs can release growth factors in vitro encouraging follicular development, and in turn, ovulation (Levi et al, 1996;Fowlkes et al, 1994;Gearing et al, 1995;Logan and Hill, 1992;Massova et al, 1998;Stouffer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%